The surgical treatment for congenital atlantoaxial dislocation - Kun WANG; Feng⁃zeng JIAN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2012)
Congenital atlantoaxial dislocation (CAAD) is one common disease of craniovertebral junction (CVJ) malformations, which diagnosis depends on CT and MRI. The treatment of CAAD is complex, as a result, the corresponding surgical techniques are different, mainly includes anterioposterior combined approach surgery, single anterior approach surgery and single posterior approach surgery. There is also simple posterior decompression surgery, but it seems not convincible. The complications related to different surgical techniques are various, hence we suggest the experienced neurosurgeons to investigate such operations.